2014
DOI: 10.1186/1471-2458-14-950
|View full text |Cite
|
Sign up to set email alerts
|

Using mobile technology to support lower-salt food choices for people with cardiovascular disease: protocol for the SaltSwitch randomized controlled trial

Abstract: BackgroundCardiovascular disease (CVD) is the leading cause of early death worldwide, responsible for an estimated 29% of all global deaths. Reducing salt intake lowers blood pressure and risk of secondary cardiac events. However, identifying low salt foods can be challenging. SaltSwitch is a simple smartphone application (app) that enables shoppers to scan the barcode of packaged foods and receive an immediate, interpretive, traffic light nutrition label on the screen, along with suggestions for healthier low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…Excessive data entry for setup and logins was reportedly undesirable (36,93,98,99). Crowdsourcing data from users was useful for providing a comprehensive back-end food database (53,58) and tailoring feedback on meal healthiness (62). Within nutrition improvement trials it was found that staggered deployment of features (rolling out new features over time) helped maintain participant engagement with the application (52).…”
Section: Evaluation Of Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive data entry for setup and logins was reportedly undesirable (36,93,98,99). Crowdsourcing data from users was useful for providing a comprehensive back-end food database (53,58) and tailoring feedback on meal healthiness (62). Within nutrition improvement trials it was found that staggered deployment of features (rolling out new features over time) helped maintain participant engagement with the application (52).…”
Section: Evaluation Of Featuresmentioning
confidence: 99%
“…Of the 4818 titles identified from the database search, 64 articles were included: 9 reporting dietary self-monitoring trials (38)(39)(40)(41)(42)(43)(44)(45)(46), 18 reporting nutritionimprovement trials (36,(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63), 30 reporting applicationdevelopment projects (37,, and 7 reporting qualitative studies with consumers (93)(94)(95)(96)(97)(98)(99). Five reports were published in 2016, 16 each in 2015 and 2014, 11 in 2013, and 16 between 2008 and 2012.…”
Section: Overviewmentioning
confidence: 99%
“…One such application of this technology involved a self-care app for salt intake, which has a protocol published for its use [6]. Although such apps are widely supported by health authorities and authors to enhance consumers’ engagement with self-management, more long-term randomized controlled trials (RCTs) are required to measure their clinical effectiveness and frequency of use [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Also, given the importance of clinical data tracking and reporting for stroke center certification, 5 a standardized electronic clinical document generated from an integrated point-of-care tool may enhance efficiency of data abstraction. Mobile applications have proven themselves promising in many facets of medicine, from public health 6,7 to medical education 8,9 to handling the coming deluge of biometrics from ''wearable technology.'' 10 There remains, however, a dearth of studies making use of mobile applications in the neurology literature.…”
Section: Introductionmentioning
confidence: 99%